2020
DOI: 10.1111/idh.12481
|View full text |Cite
|
Sign up to set email alerts
|

Research on dental plaque removal methods for efficient oral prophylaxis: With a focus on air polishing and rubber cup polishing

Abstract: Objectives: This study was conducted to compare the plaque control effectiveness of rubber cup polishing with that of air polishing during oral prophylaxis procedures and to investigate the effect of the order of air-polishing application on the efficiency of oral prophylaxis. Methods:The study included adult patients (≥20 years of age) who had visited the dental clinic for oral prophylaxis. A total of 173 subjects were divided into three groups (scaling followed by rubber cup polishing, SR; scaling followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Similar to the findings of Camboni and Donet [25], AP was found to be a superior method to RP and less damaging to the dental tissues and restorations. The results of a study conducted by Park et al confirmed that the use of AP after US for dental plaque removal can better reduce the rate of residual deposits compared to US followed by RP [26].…”
Section: Discussionmentioning
confidence: 84%
“…Similar to the findings of Camboni and Donet [25], AP was found to be a superior method to RP and less damaging to the dental tissues and restorations. The results of a study conducted by Park et al confirmed that the use of AP after US for dental plaque removal can better reduce the rate of residual deposits compared to US followed by RP [26].…”
Section: Discussionmentioning
confidence: 84%
“…However, to effectively reach this goal, a fundamental aspect is the tailoring of the maneuvers for biofilm control. During the years, great attention has been given by researchers to find new instruments capable of ideal characteristics, such as effectiveness, safety, reduced invasiveness, and maximum comfort [11]. The techniques for biofilm removal can be classified in professional and home approaches: the first ones are targeted at the elimination of both plaque and calculus from supragingival and subgingival environments, while the second ones are dedicated to removing plaque from the supragingival area.…”
Section: Introductionmentioning
confidence: 99%
“…Принцип работы заключается в подаче смеси абразивного порошка и воды в сочетании со сжатым воздухом. Такой способ позволяет быстро и эффективно удалить мягкий и плотный пигментированный налет со всех поверхностей зубов, без нагревания твердых тканей, а также сократить время визита пациента [ 11,12 ] . Несмотря на экономию времени в исследованиях A. Kaur и соавт.…”
Section: Introductionunclassified